Characterization of Post-translational Modifications of Mitochondrial RNA Polymerase and Mitochondrial Ribosomal Protein L12 - Paluch, Katelynn V; Platz, Karlie R; Gross, Matthew; Dodge, Helen; Dittenhafer-Reed, Kristin E (The FASEB journal, 2022)
Mitochondria play an important role in energy production and cellular metabolism. Mitochondria contain their own DNA (mtDNA), which encodes 13 subunits necessary for oxidative phosphorylation. Over 1500 other mitochondrial proteins, including the 77 remaining subunits required for oxidative phosphorylation and the machinery required for transcription and translation of mtDNA, are encoded by the nuclear genome. Thus, the nuclear and mitochondrial genomes must communicate to respond to the energetic needs of the cell. The mechanism of this communication is unclear. The mitochondrial proteome, including the transcriptional machinery, is subject to post-translational modifications (PTMs) such as phosphorylation of serine, threonine, and tyrosine and acylation of lysine. We hypothesize that PTMs of the mitochondrial transcriptional machinery regulate mitochondrial gene expression, akin to mechanisms controlling nuclear gene expression. Transcription of mtDNA requires three nuclear-encoded proteins: mitochondrial transcription factor A (TFAM), transcription factor B2 (TFB2M), and mitochondrial RNA polymerase (POLRMT). An accessory factor, mitochondrial ribosomal protein L12 (MRPL12), is thought to stabilize POLRMT and may promote transcription. Prior experiments in our lab show phosphorylation mimics of TFB2M have significantly reduced binding affinity for mtDNA and exhibit transcription initiation defects in vitro. Using mass spectrometry POLRMT was previously shown to be acetylated at one lysine and phosphorylated at nine amino acids, while MRPL12 contains five acetylated lysines and one phosphorylated threonine. The biochemical function of these modifications is unknown. PTMs were studied by using site-directed mutagenesis to replace the amino acid of interest to mimic acetylation (lysine to glutamine) or phosphorylation (threonine to glutamate) of POLRMT and MRPL12. Mutated proteins were purified and their mtDNA promoter binding affinity was determined by fluorescence anisotropy experiments. Fluorescence anisotropy revealed that POLRMT PTM mimics had little effect on mtDNA binding. However, when WT MRPL12 was co-incubated with WT POLRMT mtDNA binding affinity was enhanced by 30%. Increased binding affinity was lost with MRPL12 PTM mimics. WT and PTM mimics of MRPL12 were also overexpressed in mammalian cell lines. mtDNA transcript levels and mtDNA content were measured using quantitative PCR. mtDNA content was largely unchanged while some transcript-dependent effects were observed in the presence of MRPL12 protein mutants.